Penerapan Prinsip Maqashid Syariah dalam Tata Kelola Internal Perseroan Syariah: Analisis terhadap Mekanisme Eksekusi dan Perlindungan Konsumen - Regin Aeros Fidiyah (Program Studi Hukum Ekonomi Syariah, Institut Agama Islam Negeri Parepare, 2025)
This study investigates the application of maqashid sharia principles within the internal governance of Islamic corporations, using PT Bank Syariah Indonesia (BSI) as a case study in financing practices and dispute resolution. The central issue concerns the suboptimal integration of maqashid based values such as justice, protection of wealth, and public welfare into corporate decision making processes, especially in risk management for Islamic finance contracts. The objective of this study is to asses the extent to which Islamic financial institutions embed maqashid principles into internal policy and legal defense strategies, as illustrated by Indonesian Supreme Court Decisions No. 765 K/AG/2024. Employing normative juridical method, this study adopts a case based approach combined with doctrinal analysis of Islamic economic law literature and regulatory frameworks. Finding indicate that while BSI complies with formal legal structures in executing contracts, deficiencies remain In safeguarding maqashid values during asset execution processes, particularly in upholding justice and preventing harm to debtors. The court’s partial acceptance of the customer’s claim illustrates these shortcomings. This study concludes that aligning internal governance with maqashid sharia should be a foundational ethical and strategic imperative for Islamic financials institutions, ensuring that operations reflect both legal compliance and the higher objectives of Islamic law.